The dynamic capabilities as a mediating variable in the relationship between enlightened leadership and organizational change: An exploratory study at the General Company for Iraq - Sadiq Majed, Zaid (Iraqi Journal for Administrative Sciences, 2025)
The current study aims to examine the impact of enlightened leadership on organizational change in the General Company for Ports of Iraq, with a focus on the role of dynamic capabilities as a mediating variable in the relationship between the independent and dependent variables. The study population consists of employees working at the company’s headquarters, and the random sample included 300 employees. Questionnaires were distributed, with a return of approximately 277 completed forms, whose data were analyzed using SPSS and AMOS software. The results showed a positive correlation between enlightened leadership and organizational change, reflecting the impact of enlightened leadership in driving change within the company, achieving organizational goals, and improving organizational structure and culture. The study recommended supporting the enlightened leadership model in all company departments and enhancing dynamic capabilities by developing sensing systems and organizational resources. Dynamic capabilities should be integrated with leadership strategies, and a sustainable learning environment should be fostered to support leadership skills and strategic thinking towards digital transformation. Additionally, improving standardized work methods and increasing internal communication are crucial to reduce discrepancies between departments.